Resuscitation Artefacts in Forensic Autopsies - Şam, Bülent; Saka, Esra; Süner, Çiğdem (The Bulletin of Legal Medicine, 2003)
Differentiation of the antemortem, postmortem, artefactual and perimortem lesions secondary to medical interventions is a challenging task during the forensic autopsies. In this study, forensic autopsy records, performed in Istanbul between 1998-2002, were reviewed retrospectively and the cases with a resuscitation history and presenting lesions corresponding to the resuscitation were included. The location and the fetaures of the lesions, the problems arising from them were analyzed and discussed. 11.7%(n:51) of resuscitated cases had multiple rib or sternum fractures with or without bruising and 4.2%(n:19) had only bruise. Fractures were found rarely on left 3.,4. and 5. ribs from mid-clavicular line. Sternum fractures were found, with or without bruising in 3.9% (n: 17) of resuscitated cases.Key words: Forensic autopsy, CPR, artefactual lesions, malpractice, shaken baby syndrome.
Keywords: forensic autopsy; cpr; artefactual lesions; malpractice; shaken baby syndrome